Athens and Travel Literature - Mitsi, Efterpi (J. Tambling (ed.), The Palgrave Encyclopedia of Urban Literary Studies, 2021)
Athens emerges as a paradox in travel literature; it is both a site of timeless monuments and a city in constant metamorphosis. From the late seventeenth to the twenty-first century, a great number of travelogues have revealed the changing identity of Athens and the ways in which its images were circulated and interpreted through the centuries. Classical imagery became the symbol of Athens through its first detailed descriptions by early travelers, while eighteenth- and nineteenth-century scholars, writers, and artists negotiated impulses to idealize, admire, or even satirize the city Athens in their secular pilgrimages. When Athens became the capital of the new nation after the GreekWar of Independence, its symbolic significance increased, suggesting not only the continuity with antiquity but also the divided position of Greece between past and present, East and West, the ideal and the real. Following its transformation into a modern metropolis, Athens continues to challenge travel writers to capture its ambiguity and explore its mythologies and traumas.